Expression of human Krüppel‐like factor 3 in peripheral blood as a promising biomarker for acute leukemia. (26th February 2020) - Yan, Miao; Liu, Huihui; Xu, Junhui; Cen, Xinan; Wang, Qian; Xu, Weilin; Wang, Wensheng; Qiu, Zhixiang; Ou, Jinping; Dong, Yujun; Zhu, Ping; Ren, Hanyun; et al.
Abstract: Background: Universal gene targets are in persistent demand by real‐time quantitative polymerase chain reaction (RT‐qPCR)‐based methods in acute leukemia (AL) diagnosis and monitoring. Human Krüppel‐like factor 3 (hKLF3), a newly cloned human transcription factor, has proved to be a regulator of hematopoiesis. Methods: Sanger sequencing was performed in bone marrow (BM) samples from 17 AL patients for mutations in hKLF3 coding exons. hKLF3 expression in peripheral blood (PB) and BM samples from 45 AL patients was dynamically detected by RT‐qPCR. PB samples from 31 healthy donors were tested as normal controls. Results: No mutation was sequenced in hKLF3 coding exons. hKLF3 expression in PB of AL was significantly lower than that in healthy donors [0.30 (0.02‐1.07) vs 1.18 (0.62‐3.37), P  < .0001]. Primary acute myeloid leukemia (AML) exhibited the least expression values compared with secondary AML and acute lymphoblastic leukemia. Receiver operating characteristic (ROC) analyses suggested that hKLF3 expression in PB was a good marker for AML diagnosis with an AUC of 0.99 (95% CI 0.98‐1.00) and an optimum cutoff value of 0.67 (sensitivity 93.94% and specificity 93.55%). hKLF3 expression was upregulated significantly when AML patients acquired morphological complete remission (CR), and the level of hKLF3 seemed to be higher in patients with deeper CR than in patients with minimal residual disease (MRD). Paired PB and BM samples showed highly consistent alteration in hKLF3 expression ( r  = .6533, P  = .001). Besides, a significantly converse correlation between decreased hKLF3 expression in PB and markers for leukemic load was observed. Conclusions: hKLF3 expression in PB may act as a potential marker for AL diagnosis and monitoring. Abstract : In the present study, we investigated the expression of hKLF3 in acute leukemia patients by both Sanger sequencing and RT‐qPCR. ROC analyses indicated excellent efficacy of hKLF3 expression in PB samples for the diagnosis of AML. In addition, a significantly converse correlation between inhibition of hKLF3 expression in peripheral blood and increased leukemic burden was observed.